Eksplorasi Efektivitas Dua Pendekatan Pembelajaran IPA: Perspektif Guru dan Siswa terhadap Metode Eksperimen dan STAD di Madrasah Ibtidaiyah - Herawati, Isti Indah; Istiadah, Izzah Qoimatul; Putri, Denada; Pradana, Akhmad Aji (Tarunateach: Journal of Elementary School, 2025)
Science education at the Madrasah Ibtidaiyah (MI) level plays a crucial role in fostering critical thinking skills, scientific attitudes, and a fundamental understanding of scientific concepts from an early age. However, challenges such as limited facilities, diverse student characteristics, and the need to integrate Islamic values into the curriculum affect the effectiveness of science learning, particularly at MI Miftahur Rohmah Tasikharjo. This study aims to evaluate the effectiveness of using the experimental method and the cooperative learning model STAD (Student Teams Achievement Division) in improving student learning outcomes. This research employed a qualitative approach, utilizing data collection techniques through direct classroom observation and structured interviews with teachers and students. The data obtained were analyzed to determine the impact of implementing the experimental method and STAD model on students' conceptual understanding and active participation in science learning. The findings reveal that the experimental method enhances students’ understanding of science concepts through hands-on activities, observation, and independent conclusion drawing. This supports the constructivist theory, which emphasizes the active role of learners in constructing knowledge. Meanwhile, the application of the STAD model proved effective in improving teamwork, individual responsibility, and student motivation through group discussions and positive competition.